2013
DOI: 10.1021/jp408162d
|View full text |Cite
|
Sign up to set email alerts
|

Refined OPLS All-Atom Force Field Parameters for n-Pentadecane, Methyl Acetate, and Dimethyl Phosphate

Abstract: OPLS All-Atom (OPLS/AA) is a generic all-atom force field which was fine-tuned to accurately reproduce condensed phase properties of organic liquids. Its application in modeling of lipid membranes is, however, limited mainly due to the inability to correctly describe phase behavior and organization of the hydrophobic core of the model lipid bilayers. Here we report new OPLS/AA parameters for n-pentadecane, methyl acetate, and dimethyl phosphate anion. For the new force field parameters, we show very good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 36 publications
3
90
0
Order By: Relevance
“…Firstly, reliable simulation methodologies have now been developed which allow researchers to study the shear of bulk fluid systems, as well as those confined by solid surfaces. Secondly, most lubricating oils are composed of relatively large organic molecules (C 20 −C 40 ) and force-fields that govern the interactions between such molecules in MD simulations have now been refined to a stage where they can reproduce realistic viscous behaviour [8][9][10]. Finally, recent increases in computational performance coupled with the development of highly parallelised simulation algorithms to exploit multiprocessor, high performance computing (HPC) architectures, have enabled larger molecules, system sizes, and timescales to be modelled.…”
Section: The Modern Molecular Approach To Viscosity Proceeds Via the mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, reliable simulation methodologies have now been developed which allow researchers to study the shear of bulk fluid systems, as well as those confined by solid surfaces. Secondly, most lubricating oils are composed of relatively large organic molecules (C 20 −C 40 ) and force-fields that govern the interactions between such molecules in MD simulations have now been refined to a stage where they can reproduce realistic viscous behaviour [8][9][10]. Finally, recent increases in computational performance coupled with the development of highly parallelised simulation algorithms to exploit multiprocessor, high performance computing (HPC) architectures, have enabled larger molecules, system sizes, and timescales to be modelled.…”
Section: The Modern Molecular Approach To Viscosity Proceeds Via the mentioning
confidence: 99%
“…Fortunately, the latter issue has been overcome by re-parameterising AA force-fields specifically for long-chain alkanes [8,9], which has led to far more accurate density and viscosity prediction (≈ 10% for n-hexadecane [10]), even under high temperature and high pressure (HTHP) conditions [10]. More modest improvements in the density prediction of lubricantsized alkanes using AA force-fields can be made simply by reducing the intramolecular 1-4 scaling parameters for the L−J and electrostatic interactions using otherwise unmodified force-fields [80].…”
Section: Classical Force-fieldsmentioning
confidence: 99%
“…Preliminary MD runs at atmospheric pressure and temperature at 300 K were performed to equilibrate the system, whose final density was slightly less than 850 kg/m 3 , which is slightly lower than the average experimental range (860-940 kg/m 3 ) reported 46,47 for low density PE polymers. As a matter of fact, this density issue for long aliphatic chains has recently been observed 48 and corrected by a refinement procedure. Here, to circumvent this problem, an alternative approach 49 has been adopted, where all Carbon's and Hydrogen σ's in Equation (6) were reduced by 5%, achieving a final value of 890 kg/m 3 , after an equilibration time of ~ 5 ns.…”
Section: I)mentioning
confidence: 99%
“…In an MD force-field, the liquid density is mainly governed by the non-bonded (Lennard-Jones and Coulombic) interactions, whilst the viscosity is also heavily influenced by the ‘stiffness’ of the torsional potential [12,13]. Previous studies have compared all-atom and united-atom force-field performance in terms of their density and viscosity prediction of long-chain alkanes [13,14,15]; however, they have been limited to only a few variants, and have not included recent parameterizations specifically designed for long-chain molecules [16,17]. These previous comparisons have shown that united-atom force-fields consistently under-predict the viscosity of long-chain linear alkanes, with the prediction accuracy deteriorating when longer chain molecules or high pressures are used [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although improvements to the prediction of transport properties by united-atom force-fields have been made by using modified forms of non-bonded interaction (other than Lennard-Jones), such changes can often have a detrimental effect on the thermodynamic properties for which the force-fields were originally parameterized [18]. It has also been shown that many popular all-atom force-fields yield a much higher melting point for long-chain alkanes than the experimental value, which in turn leads to drastically elevated density and viscosity values [16,17,19,20]. This may be critical in simulations of confined systems, where intricate phase transitions can heavily influence the tribological behavior observed [4,21,22].…”
Section: Introductionmentioning
confidence: 99%